War in human civilization - Gat, Azar (OUP E-Books., 2006)
In this truly global study, Azar Gat sets out to unravel the 'riddle of war' throughout human history, from the early hunter-gatherers right through to the unconventional terrorism of the twenty-first century. - ;Why do people go to war? Is it rooted in human nature or is it a late cultural invention? How does war relate to the other fundamental developments in the history of human civilization? And what of war today - is it a declining phenomenon or simply changing its shape?. In this truly global study of war and civilization, Azar Gat sets out to find definitive answers to these questions i.